SPECTRAL VARIABILITY OF THE UNUSUAL SOUTHERN Be STAR HD 152478 - Pogodin, M. A.; Drake, N. A.; Jilinski, E. G.; Ortega, V. G.; de la Reza, R. (Одеські астрономічні публікації, 2010)
We present results of the spectroscopic investigation of the unusual southern Be star HD 152478. Five echelle high-resolution spectra of the object were obtained in 2007 - 2009 with the FEROS spectrograph mounted at the 2.2 m telescope of the European Southern Observatory (La Silla, Chile). The star exhibits a specific remarkable variability of the numerous line profilesofsuchelementsasHi,Hei,Feii,etc. The analysis of the spectral behaviour of the object has shown that the assumption of global oscillations in the rotating equatorial gaseous disk is not confirmed by the observations. The alternative hypothesis of a variable magnetized stellar wind of flattened geometry flowing close to the equatorial disk can qualitatively explain the observed profile variations.